2017
DOI: 10.1139/cjes-2017-0100
|View full text |Cite
|
Sign up to set email alerts
|

A middle Holocene steppe bison and paleoenvironments from the Versleuce Meadows, Whitehorse, Yukon, Canada

Abstract: Abstract:A partial skeleton of a bison was recovered during residential house construction in Whitehorse, Yukon, Canada. The specimen represents a young (estimated 6 year old) bison individual that died, was partially scavenged by carnivores, and subsequently buried by calcareous silt sediment in a pond or small lake during the middle Holocene, ϳ5400 years ago. Palaeoenvironmental data, including molluscs, pollen, vascular plant, and bryophyte macrofossils demonstrate that the small waterbody was surrounded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…4). Despite significant declines in grazing megafaunal DNA, reads extend beyond their last dated macro-remains-perhaps even as late as the mid-Holocenewhich has already been observed for Bison priscus 39,40 .…”
Section: Discussionmentioning
confidence: 91%
“…4). Despite significant declines in grazing megafaunal DNA, reads extend beyond their last dated macro-remains-perhaps even as late as the mid-Holocenewhich has already been observed for Bison priscus 39,40 .…”
Section: Discussionmentioning
confidence: 91%
“…Notwithstanding the success of the effort to conserve the two species, sharp population declines have nevertheless resulted in reduced morphological and genetic variation in the persisting populations [123,124]. Consequently, research has been dedicated to exploring the extent of the genetic variation lost in the historical bottlenecks (e.g., [125][126][127][128][129]). Similarly, accounts of the ecology and ethology of bison stem from periods when these taxa were already greatly affected by human influence [130].…”
Section: Bisonmentioning
confidence: 99%
“…Mitochondrial data have been recovered from numerous bison specimens originating from large parts of its Holarctic distribution (e.g., [125,128,129,[133][134][135][136][137][138][139][140][141][142][143]). These studies have, for instance, identified the existence of significant (but only occasionally associated) genetic and morphological variation.…”
Section: Bisonmentioning
confidence: 99%
“…The region experienced changes in the extent of glacial barriers and temporary continental connections between eastern and western Beringia via the Bering Land Bridge (Kaufman and Manley, 2004; Elias and Crocker, 2008; Burns, 2010). This dynamic physiographic backdrop has prompted questions about ecological processes that include spatial interconnectivity, biogeography and discontinuity in the landscape (Elias et al ., 2000; Elias and Crocker, 2008; Goebel et al ., 2008; Mann et al ., 2013; Heintzman et al ., 2016; Froese et al ., 2017; Potter et al ., 2017; Zazula et al ., 2017). Spatial and biogeographic questions also surround many aspects of Beringian paleoecology, including the paleo‐mobility of animals (Mann et al ., 2013; Heintzman et al ., 2016; Froese et al ., 2017) and people in Beringia (Goebel et al ., 2008; Potter et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The paleo‐mobility of steppe bison is a particular quandary because these large mobile ungulates were once spread throughout the Northern Hemisphere (Shapiro et al ., 2004; Mann et al ., 2013) but became extinct at some point during the Holocene (Stephenson et al ., 2001; Rasic and Matheus, 2007) (i.e. by at the latest ~5400 cal a bp in eastern Beringia, Zazula et al ., 2017). Our overarching aim was to improve and increase available resources to conduct research into megafaunal paleo‐mobility in eastern Beringia.…”
Section: Introductionmentioning
confidence: 99%